Hematological Malignancy Specific Patient-Reported Outcome Measure (HM-PRO): Construct Validity Study - Goswami, Pushpendra; Oliva, Esther N.; Ionova, Tatyana; Else, Roger; Kell, Jonathan; Fielding, Adele K.; Jennings, Daniel M.; Karakantza, Marina; Al-Ismail, Saad; Collins, Graham P.; McConnell, Stewart; Langton, Catherine; et al. (Frontiers in Pharmacology, 2020)
Background: Validity is the ability of an instrument to measure what it claims to measure. It means the degree to which the empirical evidence supports the trustworthiness of interpretations based on the calculated scores. The hematological malignancy (HM) specific patient reported outcome measure (HM-PRO), is a newly developed instrument for use in daily clinical practice as well as in research. This study, provides the evidence for construct validity of the HM-PRO, specifically focusing on the convergent and divergent validity compared to the other established instruments used in hematology. Methods: This validation study adopted a prospective cross-sectional design where a heterogeneous group of patients diagnosed with different HMs and different disease state were recruited. A total of 905 patients were recruited from seven secondary care hospitals in the UK and online through a patient organization. Patients were asked to complete HM-PRO and other cancer specific PRO’s, FACT-G and EORTC QLQ C-30. Data analysis was performed using IBM SPSS 23 statistical software. Results: A total of 486 males (53.7%) and 419 females (46.3%), with a mean age of 64.3 (±12.4) years and mean time since diagnosis of 4.6 (±5.2) were recruited. The total score of Part A of HM-PRO highly correlated with the five functional scales of the EORTC QLQ-C30 (Physical= -0.71,Role =-0.72, Emotional= -0.64, Cognitive= -0.58, Social= -0.74 -p<0.001). With respect to correlation with FACT-G, the total score of Part A of the HM-PRO highly correlated with Physical(-0.74), Emotional(-0.57), Functional (-0.66) domains and overall score of FACT-G (-0.74). Similarly, the total score of Part B of HM-PRO highly correlated with three symptoms scales of EORTC QLQ-C30 (Fatigue scale= -0.74, Nausea and Vomiting= -0.52, Pain= -0.59 - p<0.001) and individual symptom items (Dyspnea= 0.51,Insomnia= 0.43, Appetite loss= 0.54- p<0.001) Conclusion: The evidence on the construct validity presented in this research is a testimony of the HM-PRO’s ability to measure HRQoL issues which it intends to measure. This is of utmost importance when a PRO is used in routine clinical practice so the interpretation of the score or response to an individual item is understood by the clinicians/nurses as intended by the patients